2012
DOI: 10.1007/s10856-012-4600-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum profile of pro- and anti-inflammatory cytokines in rats following implantation of low-temperature plasma-modified titanium plates

Abstract: Surface modification of Titanium (Ti) by low-temperature plasma influences cell-material interactions. Therefore, this study aimed at examining serum cytokine levels and associations after intramuscular implantation (n = 8 rats/group) of Ti-plates with Plasma Polymerized Allyl Amine (Ti-PPAAm), Plasma Polymerized Acrylic Acid (Ti-PPAAc), and without such layers (Ti-Controls). Pro-inflammatory (IL-2, IFNγ, IL-6) and anti-inflammatory (IL-4, IL-10, IL-13) cytokines were measured weekly for 56 days. Ti-PPAAm caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…It is therefore conceivable that the increased adhesion due to hydrophilic surfaces elicits an increased inflammation. Additional data from a previous study supports a surface-dependent expression of cytokines in the serum of Lewis rats with different coated titanium implants [ 31 ]. While titanium discs coated with plasma polymerised allyl amine (positive charged, hydrophilic) induced a significant increase in pro-inflammatory cytokines IL-2 and IFN-γ, titanium discs coated with plasma polymerised acrylic acid (negative charged, hydrophobic) expressed steady and lower serum levels of IL-2 and a significant increase in anti-inflammatory IL-4 [ 31 ].…”
Section: Discussionsupporting
confidence: 60%
“…It is therefore conceivable that the increased adhesion due to hydrophilic surfaces elicits an increased inflammation. Additional data from a previous study supports a surface-dependent expression of cytokines in the serum of Lewis rats with different coated titanium implants [ 31 ]. While titanium discs coated with plasma polymerised allyl amine (positive charged, hydrophilic) induced a significant increase in pro-inflammatory cytokines IL-2 and IFN-γ, titanium discs coated with plasma polymerised acrylic acid (negative charged, hydrophobic) expressed steady and lower serum levels of IL-2 and a significant increase in anti-inflammatory IL-4 [ 31 ].…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, the serum profile of different pro- and anti-inflammatory cytokines after implantation of Ti plates with PPAAm films or plasma polymerized acrylic acid films (PPAAc) in rats was examined to characterize the systemic inflammatory response. It was found that the different plasma modifications caused distinct serum cytokine profiles, which were as a whole comparable between the PPAAm samples and the untreated controls, while the PPAAc samples differed markedly from both PPAAm and controls [32]. The serum cytokine profile for the PPAAm samples also indicated two distinct phases of the systemic inflammatory response, possibly caused by time-dependent changes in the physico-chemical properties of PPAAm as described earlier [30].…”
Section: Introductionmentioning
confidence: 67%
“…Plasma spraying, which used to be one of most popular coating techniques for implants, can be considered as one type of plasma treatment, but it has been reported to have problems such as delamination [64]. Several other types of thin coating techniques using plasma to enhance osseointegration, have been introduced and have shown some promise such as plasma nitriding [15,65], titanium nitride oxide coatings [66], plasma polymerized hexamethyldisiloxane [67], plasma polymerized allylamine [68], and plasma polymerized acrylic acid [69]. Films formed by plasma polymerization are generally free of pinholes, have a strong degree of adherence to a wide variety of materials, and have a greater degree of resistance to chemical and physical treatment because of their cross-linked structure [70].…”
Section: Surface Treatmentmentioning
confidence: 99%